Synthesis and antiaggregant and hypotensive activity of benzo-annelated azabicyclo[m.n.0]alkanes - Glushkov, V.; Stryapunina, O.; Dolzhenko, Anton; Syropyatov, B.; Shklyaev, Y. (Springer, 2009)
Three-component condensation of veratrole, isobutylene oxide, and aliphatic omega-chloronitriles via the Ritter reaction leads to 1-(omega-chloroalkyl)-6,7-dimethoxy-3,3-dimethyl-3,4-dihydroisoquinolines, the reduction of which with NaBH4 yields benzoannelated azabicyclo[m.n.0]alkanes. The synthesized compounds have been tested for hypotensive and antiaggregant activity.